The Role of Digital Economy in Reducing Economic Disparities: A Bibliometric Review - Amaluddin, Amaluddin; Payapo, Rukmuin Wida; Laitupa, Abdul Aziz (International Journal of Economics and Financial Issues, 2025)
The main objective of this study is to map scholarly articles on the area of the role of the digital economy in bridging regional economic disparity, and to establish an analytical framework of current developments, emerging trends, and future directions. This study employs a comprehensive bibliometric analysis, which includes bibliographic coupling and co-word analysis to develop an analytical framework that captures recent developments, prevailing trends, and future directions in this field. The current themes identified through bibliographic coupling highlighted that the digital economy is recognized as a crucial driver in reducing regional economic disparity through the spillover mechanism. Nevertheless, the co-word analysis identified the digital divide and uneven agglomeration as emerging trends and key challenges for regional development in the future. The originality of this study lies in its specific focus on the complex role of the digital economy in reducing regional economic disparity. To the best of the authors' knowledge, this particular intersection has not been examined exhaustively with bibliometric methods, and this study is the first of its kind in this respect, offering a nuanced understanding that bridges digital transformation research with regional development scholarship.